VO#024 Proposal of temporary beams being changed to permanent works rev.01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the revised proposal of temporary beams being changed to permanent works of BRACU new campus project.